2015
DOI: 10.1002/2015gl066306
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrostatic pressure up to 1.61 GPa on the Morin transition of hematite‐bearing rocks: Implications for planetary crustal magnetization

Abstract: We present new experimental data on the dependence of the Morin transition temperature (TM) on hydrostatic pressure up to 1.61 GPa, obtained on a well‐characterized multidomain hematite‐bearing sample from a banded iron formation. We used a nonmagnetic high‐pressure cell for pressure application and a Superconducting Quantum Interference Device magnetometer to measure the isothermal remanent magnetization (IRM) under pressure on warming from 243 K to room temperature (T0). IRM imparted at T0 under pressure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 44 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…This behavior contrasts with that of the Verwey transition temperature in magnetite, which decreases with increasing hydrostatic pressure at about −3 K/GPa (Coe et al, 2012). Bezaeva et al (2015) found that T M changes with pressure at 25 K/GPa. T M thus reaches room temperature at 1.38-1.61 GPa (Figure 28c).…”
Section: Pressure Demagnetization Behavior Of Hematitementioning
confidence: 77%
“…This behavior contrasts with that of the Verwey transition temperature in magnetite, which decreases with increasing hydrostatic pressure at about −3 K/GPa (Coe et al, 2012). Bezaeva et al (2015) found that T M changes with pressure at 25 K/GPa. T M thus reaches room temperature at 1.38-1.61 GPa (Figure 28c).…”
Section: Pressure Demagnetization Behavior Of Hematitementioning
confidence: 77%
“…Strain may cause reorientation and/or internal deformation of ferrimagnetic grains (e.g., Borradaile, 1988;Till & Moskowitz, 2014). This would lead to changes in a variety of magnetic properties, the most important of which are magnetic anisotropy, changes in remanence orientation and intensity, and changes in bulk magnetic properties such as coercivity and magnetic susceptibility (e.g., Bezaeva et al, 2015;Borradaile, 1996;Gattacceca et al, 2007;Gilder et al, 2004Gilder et al, , 2006Jackson et al, 1993;Jiang et al, 2013;Kapička, 1988Kapička, , 1992Kapička et al, 2006;Kean et al, 1976;Louzada et al, 2010). For example, up to 25% shortening due to axial compression in a set of synthetic magnetite-bearing "calcite sandstone" samples irreversibly increases their coercivity and magnetic anisotropy but decreases their mean magnetic susceptibility and the remanence component parallel to the shortening axis (Jackson et al, 1993).…”
Section: Strain-induced Magnetic Changesmentioning
confidence: 99%
“… α * for Russian alloy is 33.47 · 10 −6 1/K ( T = 333 K), 34.28 · 10 −6 1/K (348 K), 35.65 · 10 −6 1/K (373 K), 35.92 · 10 −6 1/K (378 K), and 36.20 · 10 −6 1/K ( T = 383). These calculated values from Bezaeva et al [] are in accordance with our experimental data on linear thermal expansion coefficient of Russian alloy for 333 K, 348 K, and 373 K. The β values were taken from Kagramanyan [] for suitable P , T conditions (see Table ), V S ~ V L /9. Note that this overpressure linked to heating does not apply to the 0 GPa experiment as the piston was not locked allowing dilatation without pressure increase.…”
Section: Correction Of the Pressure Demagnetizing Effectmentioning
confidence: 86%
“…The initial TRM acquisition also occurs at a higher pressure than the nominal RT one. The pressure change inside the cell was first calculated as a function of applied temperature, following the model of Bezaeva et al [2015], using the thermal expansion parameters of the cell and of the PES-1 liquid:…”
Section: Correction Of the Pressure Demagnetizing Effectmentioning
confidence: 99%
See 1 more Smart Citation